Novel techniques in upper aerodigestive tract endoscopy - Hörmann, Karl; Riedel, Frank (Nihon-Kikan-Shokudōka-Gakkai-Kaihō, 2004)
Since Kilian in 1893 first used the rigid endoscope and Ikeda 1964 invented the flexible bronchoscope, novel techniques have been introduced in bronchoesophagoscopy with increasing speed within the last decades. Videoendoscopy technology carries a great diagnostic potential due to optimal insight even in small diameters. PH-monitoring (PH-metry) defines GERD (gastroesophageal reflux disease) and LPR (laryngopharyngeal reflux) related diagnosis. Fiber-optic endoscopic evaluation of swallowing with sensory testing (FEESST) and transnasal esophagoscopy are new and innovative tools for non-invasive decision making. The use of light therapy for tissue destruction is highly attractive for the endoscopic and minimally invasive therapy of esophageal cancer. Photodynamic therapy (PDT) offers the possibility of palliation of advanced obstructing tumours, treatment of obstruction to an esophageal prosthesis, or eradication of early asymptomatic mucosal disease. Electrosurgery, radio-frequency systems, argon plasma coagulation (APC) and laser surgery all offer techniques, instruments, equipment and systems for resecting and destroying mucosal lesions and for hemostasis in the upper aerodigestive tract. Self-expanding metallic stents have assumed increasing importance in the palliative treatment of malignant dysphagia in recent years. Stents are also occasionally used as a last resort in benign disease. Percutaneous endoscopic tracheostomy and gastrostomy are bedside procedures for fast rehabilitation. Aim of this review is to present recent advances in the field of upper aerodigestive tract endoscopy.
Gesehen am 19.04.2022